Physical activity improves the visual–spatial working memory of individuals with mild cognitive impairment or Alzheimer’s disease: a systematic review and network meta-analysis - Deng, Jie; Wang, Hong; Fu, Tingting; Xu, Chong; Zhu, Qiqi; Guo, Liya; Zhu, Yu (Frontiers in Public Health, 2024)
Objective: Our network meta-analysis aimed to ascertain the effect of physical activity on the visual-spatial working memory of individuals with mild cognitive impairment and Alzheimer's disease as well as to propose tailored exercise interventions for each group.Methods: Employing a frequentist approach, we performed a network meta-analysis to compare the effectiveness of different exercise interventions in improving the visual-spatial working memory of individuals with mild cognitive impairment and Alzheimer's disease. Subsequently, we explored the moderating variables influencing the effectiveness of the exercise interventions through a subgroup analysis.Results: We included 34 articles involving 3,074 participants in the meta-analysis, comprised of 1,537 participants from studies on mild cognitive impairment and 1,537 participants from studies on Alzheimer's disease. The articles included exhibited an average quality score of 6.6 (score studies) and 6.75 (reaction time [RT] studies), all passing the inconsistency test (p>0.05). In the mild cognitive impairment literature, mind-body exercise emerged as the most effective exercise intervention (SMD=0.61,95% CI: 0.07-1.14). In Alzheimer's disease research, aerobic exercise was identified as the optimal exercise intervention (SMD=0.39,95% CI: 0.06-0.71).The results of the subgroup analysis suggest that the most effective approach to enhancing the visual-spatial working memory of individuals with mild cognitive impairment entails exercising at a frequency of three or more times per week for over 60 minutes each time and at a moderate intensity for more than three months. Suitable exercise options include mind-body exercise, multicomponent exercise, resistance exercise, and aerobic exercise. For individuals with Alzheimer's disease, we recommend moderately intense exercise twice per week for over 90 minutes per session and for a duration of three months or longer, with exercise options encompassing aerobic exercise and resistance exercise.